When clay sings - Baylor, Byrd.; Bahti, Tom (New York : Scribner, 1972)
The daily life and customs of prehistoric southwest Indian tribes are retraced from the designs on the remains of their pottery.
Mode of access: Internet.
SPEC WALP: In the Lee Walp Family Juvenile Book Collection, Gift of the Lee Walp Family. In dust jacket. Manuscript notes by Lee Walp.
Keywords: Indigenous peoples -- Southwest, New -- Juvenile literature; Indigenous pottery -- North America -- Juvenile literature; Indians of North America -- Southwest, New -- Juvenile literature; Indian pottery -- North America -- Juvenile literature